Criminal Provisions in Government Regulation Number 9 of 1975 According to Law Number 12 of 2011 - Zulham, Zulham; Pagar, Pagar; Latip, Muhammad (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
This paper aims at explaining the criminal provisions in government regulation number 9 of 1975, according to Law Number 12 of 2011. The research method used in conducting this article is a qualitative research method with a normative juridical research type using the statute approach. Sources of data are divided into two forms, namely primary data sources obtained directly from main sources such as the head of the Regional Office of the Ministry of Religions of the Republic of Indonesia, Commission III of the House of Representatives of the Republic of Indonesia, the Head of the High Court of Religion of North Sumatra, and Experts in the field of Islamic Law. In addition, laws and regulations and the book of ushul fiqh are used as secondary materials. Data analysis was carried out in the stages of data reduction, data presentation, and conclusion. The results show that the criteria for marriage that can be punished or fined are divided into two, namely, First, is the presence of intention. Second, the action is detrimental to another person, in other words, the injured person reports or complains about the detrimental action to the police so that it can be processed because the provision is a complaint offense. Tulisan ini bertujuan untuk menjelaskan ketentuan pidana dalam peraturan pemerintah nomor 9 tahun 1975 menurut Undang-Undang Nomor 12 Tahun 2011. Adapun metode penelitian yang digunakan dalam penulisan artikel ini adalah metode penelitian kualitatif dengan jenis penelitian yuridis normative menggunakan pendekatan statute approach. Sumber data terbagi pada dua bentuk yaitu sumber data primer yang diperoleh langsung dari sumber utama seperti Kepala Kanwil Kementerian Agama RI, Komisi III DPR RI, Ketua Pengadilan Tinggi Agama Sumatera Utara, dan Pakar dibidang hukum Islam. Selain itu, peraturan perundang-undangan dan kitab ushul fiqih dijadikan sebagai bahan sekunder. Analisis data dilakukan dengan tahapan reduksi data, penyajian data, dan kesimpulan. Hasil penelitian menunjukkan bahwa kriteria pernikahan yang dapat dipidana atau didenda terbagi kepada dua, yaitu; Pertama, adalah adanya niat atau unsur kesengajaan. Kedua, tindakan tersebut merugikan orang lain, dengan kata lain, bahwa orang yang dirugikan tersebut melaporkan atau mengadukan perbuatan yang merugikannya kepada pihak kepolisian, sehingga dapat diproses, karena ketentuan tersebut merupakan delik aduan.